Organizing Sumber Daya Panti Asuhan Muhammadiyah Lhokseumawe dalam Pembinaan Akhlak Anak Asuh - Almuhajir Almuhajir (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aims to explain the organizing of Muhammadiyah Lhokseumawe orphanage resources in fostering the morals of foster children. This research is a qualitative research using a phenomenology approach. The results showed that organizing the resources of the Muhammadiyah Lhokseumawe orphanage in the moral formation of foster children globally had carried out their duties and mutual coordination. The Chair, coordinates and evaluates the management and cooperation with various stakeholders, both government and private. Secretary, takes care of internal and external administration of the institution. Finance, records, compiles and oversees the entry and exit of money from various parties for the needs of foster children. The field of Education, Supervision and Order is responsible for formal and non-formal education of foster children, supervises various activities, and cooperates with third parties in handling security. The field of Health and Hygiene, handles the health and hygiene of foster children both practically and in a mindset. Various job descriptors that are in the management structure of Muhammadiyah Orphanage in Lhokseumawe, handling the problem of the moral development of foster children are fully entrusted to the field of care.